Rectangular Dielectric Resonator Antennas Theory and Design - Yaduvanshi, Rajveer S.; Parthasarathy, Harish; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
This book covers resonating modes inside device and gives insights into antenna design, impedance and radiation patterns. It discusses how higher-order modes generation and control impact bandwidth and antenna gain. The text covers new approaches in antenna design by investigation hybrid modes, H_Z and E_Z fields available simultaneously, and analysis and modelling on modes with practical applications in antenna design. The book will be prove useful to students, researchers and professionals alike.
Rectangular DRA fundamental  background -- Rectangular DRA resonant modes and sources -- Mathematical analysis of Rectangular DRA -- Mathematical analysis of transcendental equation in rectangular DRA.-  Mathematical analysis of  RDRA amplitude coefficients -- Mathematical analysis of radiation pattern of RDRA -- Rectangular DRA  higher order modes and experimentations -- RDRA in  input  angular excitation mathematical model and resonant  modes -- Sensitivity Analysis Rectangular  DRA -- Hybrid modes in RDRA -- Inhomogeneous permittivity, permeability and conductivity solution in rectangular DRA -- Case Study 1-Structure and hardware experimentations -- Case Study 2-RDRA with manganese- manganese material as dielectric -- Case Study 3-Dual feed RDRA hardware and measurements -- Case Study 4-Isolated and Grounded RDRA -- Annexure 1-Details of Dielectric materials and their suppliers -- Annexure 2-Two dimensional mathematical model of resonant modes in cavity resonator -- Annexure 3-Design steps of RDRA using  A.D.S software -- Annexure 4-Resonating Modes in Rectangular Resonators -- Annexure 5-Resonant mode generation and control  in RDRA -- Annexure 6-Cartesian, cylindrical and spherical coordinate system -- References -- Index Terms.
Keywords: Telecommunication; Lasers; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks; Laser